2005
DOI: 10.1093/jac/dki172
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis for the evaluation of lopinavir/ritonavir-versus efavirenz-based HAART regimens in antiretroviral-naive HIV-positive patients: results from the Italian MASTER Cohort

Abstract: Although comparisons of drug efficacy in non-randomized studies should be viewed with caution, from a virological point of view efavirenz-containing regimens performed as well (on-treatment analysis) or better (ITT analysis) than those containing lopinavir/ritonavir. In contrast, immunological outcome appeared to favour lopinavir/ritonavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
5
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 11 publications
3
30
5
1
Order By: Relevance
“…32 The efavirenz-containing regimens in this study were associated with a nearly 300-cells/mm 3 increase in CD4 cell count over baseline over 3 years. Although some have suggested that NNRTI-based regimens are inferior to PI-based regimens in CD4 cell count recovery, [33][34][35] our results appear comparable with results from long-term PI studies. 36 Genotypic evidence of resistance to NNRTIs was detected in stored samples from 8% of patients at baseline who would start an efavirenz-containing regimen and ultimately experience virologic failure.…”
Section: Commentsupporting
confidence: 68%
“…32 The efavirenz-containing regimens in this study were associated with a nearly 300-cells/mm 3 increase in CD4 cell count over baseline over 3 years. Although some have suggested that NNRTI-based regimens are inferior to PI-based regimens in CD4 cell count recovery, [33][34][35] our results appear comparable with results from long-term PI studies. 36 Genotypic evidence of resistance to NNRTIs was detected in stored samples from 8% of patients at baseline who would start an efavirenz-containing regimen and ultimately experience virologic failure.…”
Section: Commentsupporting
confidence: 68%
“…Conversely to what has been shown in these studies, [3][4][5][6] we found that the CD4 + count increase was significantly lower in the LPV/r group despite the fact that all the patients had an undetectable level of plasma viremia after 48 weeks of cART. The Lake study also showed that patients on LPV/r-containing regimens had a lower CD4 + count increase, although the differences were not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…3 Similar findings have been reported in other cohort studies. [4][5][6] Conversely, other clinical trials that compared NNRTI and PI-based regimens did not find significant differences in the increases in CD4 + counts in both groups. [7][8][9] It is unclear if the potential differences in recovery of the CD4 T cell count with different cART regimens have any clinical or immunological relevance.…”
Section: Introductionmentioning
confidence: 80%
“…Four large studies comparing ART in treatmentnaive patients using either an NNRTI-or a PI-based cART for a maximum follow-up of 32 months found comparable responses of CD4 + T cell count [17][18][19][20]. However, other studies found smaller increases in CD4 + T cell count in individuals using an NNRTI-based cART at 48 and 96 weeks [21][22][23]. In the present study, we analyzed the long-term CD4 + T cell recovery in 3293 patients of the Swiss HIV Cohort Study (SHCS) who received the first cART that included a nonboosted PI, NNRTI, or a boosted PI.…”
mentioning
confidence: 99%